La inteligencia emocional en el periodo de ambientación de los niños de la inicial i, de la unidad educativa” Luis Cordero Crespo”, Parroquia Palmira, Cantón Guamote, Provincia De Chimborazo Periodo 2017 – 2018 - Tixi Daquilema, José Humberto (2018)
Research as the main objective to determine the importance of the development of Emotional Intelligence in the Setting Period of the children of Initial I, of the Educational Unit "Luis Cordero Crespo", Parish Palmira, Guamote Canton, Province of Chimborazo Period 2017 - 2018, to diagnose this problem that exists in children. In this reason we worked with a population of 10 students among boys and girls of Initial Level 1, non-experimental type inquiry since none of the variables was manipulated, that is to say; the problem investigated was studied as it was given in context, proceeded to the study of the problem in order to know the multiple benefits that would be granted to the human being if they will be given the necessary tools and each of the children will develop their emotional intelligence, this can be achieved especially in the period of the children's environment, that is to say when they have started their student life or setting, the type of research is descriptive and field, since the research work was done in the " CECIB ", taking the information of the elements involved where the problem is noticed; examining the explanations, causes and effects of the given problem, with descriptive design since it will serve to describe the two variables; the observation technique was used since it clearly captures the object under investigation, the observation cards being the instrument for the analysis of the problem, which allowed analyzing and interpreting the results, concluding that this inquiry will contribute to the integral development of the children what It will benefit if the teachers of Initial take into consideration the development of the intelligences in the children from very early ages.